2014
DOI: 10.4137/cmo.s12701
|View full text |Cite
|
Sign up to set email alerts
|

Folate Levels and Polymorphisms in the Genes MTHFR, MTR, and TS in Colorectal Cancer

Abstract: AIMThe aim of the study was to explore and describe the effect of polymorphisms in folate-associated genes regarding the levels of different folate forms and their distribution in tumors and mucosa in patients with colorectal cancer.MATERIALS AND METHODSTumor and mucosa tissues from 53 patients with colorectal cancer were analyzed. The concentrations of tetrahydrofolate (THF), 5-methylTHF, and 5,10-methyleneTHF were measured by liquid chromatography—mass spectrometry. Genotyping of polymorphisms in the folate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The need for metabolic activation of LV could provide for interindividual differences in its utilization that could affect the potential benefit gained from the LV addition. Previous results, including findings of our own research group [ 12 ], have showed that the variation in folate levels in tumor and mucosa tissues between patients is significant. The continued advances in genetics and metabolomics provide new possibilities for advanced studies of the folate metabolism and enables greater understanding of the interplay between folates and enzymes targeted by different chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 88%
“…The need for metabolic activation of LV could provide for interindividual differences in its utilization that could affect the potential benefit gained from the LV addition. Previous results, including findings of our own research group [ 12 ], have showed that the variation in folate levels in tumor and mucosa tissues between patients is significant. The continued advances in genetics and metabolomics provide new possibilities for advanced studies of the folate metabolism and enables greater understanding of the interplay between folates and enzymes targeted by different chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 88%
“…Thus, the actual concentration of methyleneTHF, and not only of total folates, can now be measured in tissue samples. As evidenced by our recent findings, using the novel method, there is a significant variability in the folate levels in tumour and mucosa tissues between patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leucovorin or folinic acid is converted in vivo into the biologically active metabolite folate and enhances the effect of 5-fluorouracil (5-FU) in colorectal cancer. 5-FU is metabolized to the active metabolite 5-fluoro-2′-deoxyuridine 5′-monophosphate (FdUMP), binding to and inhibiting the enzyme thymidylate synthase (TS) 123 . Folinic acid is rapidly metabolized to 5, 10-methylenetetrahydrofolate (5,10-CH 2 -THF), 5, 10-methenyltetrahydrofolate (5, 10-CH=THF), and then to 5-methyltetrahydrofolate (5-MTHF) 123124 .…”
Section: A Novel Application: 3d Cell Culture Systemsmentioning
confidence: 99%